Leshon Limmudim: essays on the language and literature of the Hebrew Bible in honour of A. A. Macintosh - Baer, David; Macintosh, A. A.; Gordon, Robert P.; Baer, David (Library of Hebrew bible/Old Testament studies, 2013)
Bibliogr. A. A. Macintosh S. [XXIII] - XXIV